Analisis Komunikasi Dakwah Interpersonal : Studi Kasus di Lingkungan Keluarga Muslim - Adhi Kusuma; Gama Rasa Abdul Aziz; Dahlia Pusvita Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
Interpersonal da'wah communication is a process of conveying Islamic messages that takes place directly between family members, both verbally through advice and conversation, and nonverbally through exemplary attitudes and behavior. This communication is two-way, contextual, and based on affection and empathy. This study is the effectiveness of interpersonal da'wah communication in shaping the Islamic character of family members. The results of the analysis show that this communication is very effective because it is supported by emotional closeness between family members, continuity in daily interactions, and the strong role of parents or other family members as role models in implementing Islamic values. In addition, habituation through joint worship practices, social ethics, and the use of religious language also strengthen the internalization of Islamic values. Thus, the family is not only a place of shelter, but also functions as the first madrasah which is very strategic in shaping Muslim individuals who are faithful, pious, and have noble morals from an early age.